Methods of Hearing Preservation during Cochlear Implantation - Khater,Ahmed (2017)
Abstract Introduction Recent advances in surgical techniques and electrode design have made residual hearing preservation during cochlear implantation (CI) possible, achievable, and desirable. Objectives The objective of this study was to review the literature regarding methods used for hearing preservation during CI surgery. Data Synthesis We performed a search in the LILACS, MEDLINE, SciELO, PubMed databases, and Cochrane Library, using the keywords CI, hearing preservation, CI electrode design, and CI soft surgery. We fully read about 15 studies that met the criteria described in “study selection”. The studies showed that several factors could contribute to possible cochlear damage during or after CI surgery and must be kept in mind; mechanical damage during electrode insertion, shock waves in the perilymph fluid due to implantation, acoustic trauma due to drilling, loss of perilymph and disruption of inner ear fluid homeostasis, potential bacterial infection, and secondary intracochlear fibrous tissue formation. The desire to preserve residual hearing has led to the development of the soft-surgery protocols with its various components; avoiding entry of blood into the cochlea and the use of hyaluronate seem to be reasonably supported, whereas the use of topical steroids is questionable. The site of entry into the cochlea, electrode design, and the depth of insertion are also important contributing factors. Conclusion Hearing preservation would be useful for CI patients to benefit from the residual low frequency, as well as for the children who could be candidate for future regenerative hair cell therapy.